Antioxidant, Cytotoxic, Membrane Stabilizing and Antimicrobial Activities of Bark and Seed of Entada phaseoloides (L.) Merr.: A Medicinal Plant from Chittagong Hill Tracts - Fahima Aktar,; Md. Ruhul,; Sk. Omar Faruque,; Farhana Rumi,; Mohiuddin Abdul,; Mohammad A. Rashid, (Journal of Pharmacy and Nutrition Sciences, 2011)
The methanolic crude extract of the bark and seed of Entada phaseoloides (L.) Merr. and its different organic soluble partitionates were screened for antioxidant, cytotoxic, membrane stabilizing and antimicrobial activities. The crude extract and carbon tetrachloride and aqueous soluble fractionsof both bark and seed showed higher level of total phenolic content (TPC, 245.59, 240.22, 240.03 & 117.0 mg of GAE/gm of dried extract). In the DPPH assay, the crude extract of bark and its chloroform and aqueous soluble fractions demonstrated strong antioxidant property with the IC50 of 3.24, 1.55 and 3.6 μg/ml, respectively whereas all the fractions of seed extract revealed mild antioxidant activity. The petroleum ether soluble fraction of both seed and bark exhibited significant cytotoxicity (LC50 = 1.54 & 5.4 μg/ml) which confers the presence of bioactive metabolites in this plant. On the other hand, the crude extract of seed and petroleum ether soluble fraction of bark inhibited the hemolysis of RBC of rat’s blood by 78.89 and 57.43%, respectively as compared to 84.44% exerted by acetyl salicylic acid (0.10 mg/ml). In antimicrobial screening, the carbon tetrachloride soluble fraction of bark showed significant antimicrobial activity against Staphylococcus aureus (zone of inhibition = 17.0 mm) with MIC and MBC values of 7.81 μg/ml and 125 μg/ml, respectively